A rare metabolic complication of acute lymphoblastic leukemia in childhood: lactic acidosis - Gökçe, Müge; Ünal, Şule; Gülşen, Hayriye; Başaran, Özge; Çetin, Mualla; Gümrük, Fatma; Beşbaş, Nesrin; Gürgey, Aytemiz (The Turkish Journal of Pediatrics, 2012)
A 13-year-old boy presented with nausea, fatigue, weight loss, and bone pain for two months. Complete blood count and serum renal and liver function tests were all normal. Blood gas analysis revealed severe metabolic acidosis with high anion gap. Lactate level was 61.2 mmol/L. Abdominal ultrasonography yielded bilateral nephromegaly and hepatomegaly with increased echogenicity. Peripheral blood smear revealed 2% blasts. Bone marrow aspiration showed ’Common ALL Antigen’-negative acute lymphoblastic leukemia by flow cytometric analysis. Metabolic acidosis dissolved as soon as chemotherapy was begun. Lactic acidosis at the presentation of acute lymphoblastic leukemia–especially with low tumor burden–is a very rare and almost always fatal complication. Our patient is still alive and in remission, which is a point of interest in this child.